Management of Ventilator-associated Pneumonia - Ferrer, M. (Yearbook of Intensive Care and Emergency Medicine, 2008)
Pneumonia is the most important respiratory infection in mechanically ventilated patients. It is defined as the presence of microorganisms in the pulmonary parenchyma leading to the development of an inflammatory response by the host, which may be localized in the lung or may extend systemically. Nosocomial pneumonia is an infectious process which develops within 48 hours after admission to the hospital and that was not incubating at the time of hospitalization. Ventilator-associated pneumonia (VAP) is considered as a subgroup of nosocomial pneumonia and is an infectious pulmonary process which develops 48 hours after the presence of an artificial airway and mechanical ventilation. Since a large proportion of the patients who develop nosocomial pneumonia are intubated and receive mechanical ventilation, most epidemiological and clinical studies on nosocomial pneumonia have been focused on critically ill patients and those receiving mechanical ventilation. From a clinical point of view, nosocomial pneumonia is of great importance not only because of the consequences of the important morbidity and mortality but also due to the high costs associated with development of this disease.